2014
DOI: 10.3109/09638288.2014.935874
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between goal intentions and actions: a systematic review in patient populations

Abstract: Purpose: To evaluate the evidence for the effectiveness of if-then implementation intentions (if-then plans) in adult patient populations. Outcomes of interest included adherence, goal pursuit and physical health outcomes.Method: Keywords were used to search electronic databases without date or language restrictions (up to 30/4/14). Studies were included if they 1) concerned a patient population; 2) used if-then plans as a sole intervention or as part of treatment, therapy or rehabilitation; 3) if they were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Previous studies of implementation intentions in clinical populations have not specifically explored if-then plans [33]. This study highlights that if-then' plans are feasible and acceptable in bridging the goal intention-action gap in rehabilitation with people with MS and stroke, who are experiencing difficulties with mobility.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies of implementation intentions in clinical populations have not specifically explored if-then plans [33]. This study highlights that if-then' plans are feasible and acceptable in bridging the goal intention-action gap in rehabilitation with people with MS and stroke, who are experiencing difficulties with mobility.…”
Section: Discussionmentioning
confidence: 74%
“…Our recent systematic review of this approach with clinical populations revealed four studies that had used this successfully [33]. These studies showed that people who form if-then plans achieve better outcomes on medication adherence (in epilepsy and stroke) [34][35][36], physical capacity (when combined with Mental Contrasting & Cognitive Behavioural Therapy in chronic back pain) [37], and physical activity (in obese older adults) [38] than controls.…”
Section: Introductionmentioning
confidence: 96%
“…Third, previous research has shown that formulating goal intentions does not necessarily translate into goal‐directed behavior or goal attainment, a discrepancy commonly referred to as the intention‐behavior gap . Keeping a healthy lifestyle requires continued effort from the patients themselves, and the results of this study indicate that it takes >4 phone calls to support patients in maintaining healthy behaviors over time.…”
Section: Discussionmentioning
confidence: 79%
“…Screening and provision of educational interventions may address cognitive factors relating to psychological considerations, such as past and current maladaptive coping strategies, available coping resources and supports, knowledge of stressors, and adaptive-positive coping strategies. Evidence-based cognitive coping strategies may include imagery, relaxation techniques (breathing, progressive muscle relaxation), positive self-talk, and goal-setting (Covassin, Beidler, Ostrowksi, & Wallace, 2015;Granquist et al, 2014;Kersten, McCambridge, Kayes, Theadom, & McPherson, 2015).…”
Section: Implications For Using the Proposed Adapted Biopsychosocial mentioning
confidence: 99%